Use Of Invasive Blood Pressure Monitoring In Asymptomatic Mildly Hypotensive Cardiac Patients - Rawat, Bharat; Karki, DB; Vaidhya, Abhinav; Gurung, Jessen; Shah, Ajay; Acharya, Subhash; Sodhi, HS; Pandey, M; Pande, R (Nepalese Heart Journal, 2004)
Beta-blockers and Angiotensin Converting Enzme Inhibitor (ACE-I) are still underused drugs by CAD or CHF patients. ’ Patients with mild hypotension (noninvasive Systolic Blood Pressure (SBP): 80 — 90mm Hg) are often not prescribed these medications.